In the blue pharmacy essays on poetry and other transformations - Boruch, Marianne, 1950- (Trinity University Press, 2005)
"Sixteen essays on poets and poetry, the writing life, and how the imagination works with mystery and surprise in a variety of poets from Elizabeth Bishop to Theodore Roethke"--Provided by publisher.